Airborne remote sensing of clouds and precipitation using Ka- and W-band - Hagen, Martin; Delanoe, Julien; Groß, Silke; Hirsch, Lutz (2015)
The German research aircraft HALO (High Altitude Long range aircraft) can be equipped with a remote sensing payload to study cloud properties and water vapor profiles of the atmosphere. This package was first flown during the NARVAL (Next-generation Aircraft Remote sensing for VALidation studies) mission in December 2013 and January 2014. New missions are planned for 2016. The HALO microwave package (HAMP) consists of a cloud radar and microwave radiometers. The cloud radar is a nadir pointing Ka-band radar (35 GHz). The microwave radar radiometers are operating at 26 frequency channels in the K-band, V-band, W-band, F-band, and G-band. The active and passive microwave measurements are complemented by a water vapour and high spectral resolution lidar. During the NARVAL campaign a joint flight with the French research aircraft Falcon 20 carrying the RASTA radar was performed over France over a distance of about 500 km. The RASTA cloud radar is a multi-beam radar operating at W-band (95 GHz). While the Falcon was flying at cloud top at about 10 km MSL, HALO was flying at 12.5 km MSL. The complete joint flight was over clouds which were also precipitating for about half of the joint flight track. The differences in reflectivities observed at both wavelengths are negligible for the 3 - 4 km deep non-precipitating cloud. The difference is getting more significant (app. 15 dB) in an about 2 km deep layer above the melting layer. In rain the difference is up to 30 dB, due to differential attenuation (in rain and above the melting layer) and the fact that reflectivity at W-band of raindrops is limited due to Mie scatter when the size of the drops is in the same order like the wave-length. Additionally, the HALO Ka-band radar provides measurements of the linear depolarization ratio LDR. The combination of both radar observations at different wave length allows for the estimation of the properties of cloud and precipitation particles due to differential attenuation. This can provide more information than will be possible ...